Kinship network evolution in Argentina. An exploration based on online data - Larrosa, Juan M. C.; Galgano, Franco; Gutiérrez, Emiliano (AWARI, 2023)
We present the initial stages of a research project for a big data genealogical study. Consanguineous ties among members of a family form kinship networks. Family is the first social network for actors and historically was the source of education, support, and socialization. Family is still the source of power in the royalty, and family business has commonly been the first stage for future big firms. Nepotism is still a usual practice in politics and civil service. We analyze contributions to population evolution and propose to empirical test theoretical results. For that to be accomplished, we gather online data and present an initial descriptive analysis. In the end, following previous contributions, we also extend data usage for identifying historical lineages from colonial times in Argentina and analyzing if that antecedent portrays different benefits to descendants.